2018
DOI: 10.21873/anticanres.12732
|View full text |Cite
|
Sign up to set email alerts
|

Possible Application of Ascites-infiltrating Gamma-delta T Cells for Adoptive Immunotherapy

Abstract: Vδ T cells in AILs are cytotoxic to tumour cells in ascites and may be considered in adoptive immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In this study, the ratio Vδ2 + T cells in CD3 + cells in the ascitic fluid obtained from a CART filter was 1.2%, which was similar to the ratio of cells obtained from the peripheral blood. Reportedly, the growth rate of γδ T cells in the ascitic fluid of patients with ovarian cancer who underwent direct paracentesis with 2M3B1-PP and IL2 was 1.9 times and 3.8 times with Zol and IL2 8) ,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the ratio Vδ2 + T cells in CD3 + cells in the ascitic fluid obtained from a CART filter was 1.2%, which was similar to the ratio of cells obtained from the peripheral blood. Reportedly, the growth rate of γδ T cells in the ascitic fluid of patients with ovarian cancer who underwent direct paracentesis with 2M3B1-PP and IL2 was 1.9 times and 3.8 times with Zol and IL2 8) ,…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the ratio of Vδ2 + T cells in CD3 + cells of PBMC in 24 patients with ovarian cancer, fallopian tube cancer and peritoneal carcinoma were 1.42% 8) . In this study, the ratio Vδ2 + T cells in CD3 + cells in the ascitic fluid obtained from a CART filter was 1.2%, which was similar to the ratio of cells obtained from the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cachexia in humans can be exacerbated if deficiencies occur in essential nutrients 7,8 , for example long-chain fatty acids and vitamin D, whose uptake is facilitated by pancreatic enzymes such as lipase. The administration of fatty acids increases skeletal-muscle mass in people with pancreatic cancer, particularly when this supplementation is combined with pancreatic enzymes 9 .…”
Section: J M At T H I a S L ö H Rmentioning
confidence: 99%